Association between Sjögren syndrome, sociodemographic factors, comorbid conditions, and optic neuritis: a Taiwanese population-based study - Jan, Ren-Long; Ho, Chung-Han; Sung, Cheng-Hao; Wang, Jhi-Joung; Jan, Han-Yi; Chen, Wei-Yu; Chang, Yuh-Shin (Frontiers in Neurology, 2024)
Purpose Our study aimed to explore the correlation between Sjögren syndrome, sociodemographic factors, comorbid conditions, and optic neuritis. Methods This retrospective, nationwide, population-based, matched case–control investigation involved 33,190 individuals diagnosed with optic neuritis, identified using the International Classification of Diseases, Ninth Revision, Clinical Modification codes 377.30 for optic neuritis or 377.32 for retrobulbar neuritis. Patient data were extracted from the Taiwan National Health Insurance Research Database. Demographic characteristics, the presence of Sjögren syndrome, and pre-existing comorbid conditions were analyzed using univariate logistic regression. Continuous variables were assessed with a paired t-test. Adjusted logistic regression was employed to compare the prognosis odds ratio (OR) of patients with optic neuritis to controls. Results After adjusting for confounding variables, individuals with Sjögren syndrome exhibited a significantly higher likelihood of developing optic neuritis compared to controls (adjusted OR, 9.79; 95% confidence interval [CI], 7.28–12.98; p < 0.0001). Other conditions associated with increased odds of optic neuritis included rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis, systemic lupus erythematosus, and granulomatous vasculitis (adjusted OR: 1.57, 95% CI: 1.33–1.86; adjusted OR: 2.02, 95% CI: 1.65–2.48; adjusted OR: 140.77, 95% CI: 35.02–565.85; adjusted OR: 2.38, 95% CI: 1.71–3.30; adjusted OR: 18.28, 95% CI: 2.21–151.45, respectively), as well as systemic infections such as human herpes viral infection and tuberculosis infection (adjusted OR: 1.50, 95% CI: 1.35–1.66; adjusted OR: 4.60, 95% CI: 3.81–5.56, respectively). Discussion Our findings strongly support the existence of an association between Sjögren syndrome, rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis, systemic lupus erythematosus, granulomatous vasculitis, human herpes viral infection, tuberculosis, and optic neuritis.